1998
DOI: 10.1111/j.2042-3306.1998.tb05132.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased glucose metabolism causes separation of hoof lamellae in vitro: a trigger for laminitis?

Abstract: Glucose consumption by the hoof explants was inhibited by 2-deoxyglucose and aminophenylmercuric acetate. The explants consumed relatively large amounts of glucose during the first 2 days of incubation and then little over the next 6 days.Despite the reduced glucose consumption, the hoof explants did not separate over 8 days of incubation. The results indicated that the integrity of the hoof explants was initially dependent on consumption of glucose and provide a possible explanation for the development of lam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 21 publications
(19 reference statements)
2
64
0
1
Order By: Relevance
“…It has been demonstrated that decreased glucose availability causes separation of hoof lamellae in vitro suggesting insulin resistance may be involved in the pathogenesis of laminitis by decreasing laminar glucose metabolism (Pass et al 1998;Treiber et al 2006a). Glucocorticoids are suggested to precipitate laminitis (Eustace and Redden 1990) and in agreement recent studies have shown that dexamethasone treatment can induce insulin resistance in horses (Firshman et al 2005;Tiley et al 2007Tiley et al , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that decreased glucose availability causes separation of hoof lamellae in vitro suggesting insulin resistance may be involved in the pathogenesis of laminitis by decreasing laminar glucose metabolism (Pass et al 1998;Treiber et al 2006a). Glucocorticoids are suggested to precipitate laminitis (Eustace and Redden 1990) and in agreement recent studies have shown that dexamethasone treatment can induce insulin resistance in horses (Firshman et al 2005;Tiley et al 2007Tiley et al , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…This theory is derived from the observation that, using an in vitro explant model, hoof lamellar keratinocytes were shown to have a critical glucose Laminitis and the Equine Metabolic Syndrome 241 requirement and that keratinocyte separation from underlying basement membrane occurs when glucose is insufficient. 39 More recently, insulin has been shown to not affect glucose uptake through HLI explants and the insulin-dependent glucose transporter (GLUT-4) is not present in hoof keratinocytes. 40 Therefore, if glucose dysregulation is pivotal to the risk for laminitis associated with IR, it is not based on an insulin-dependent glucose uptake mechanism through hoof-lamellar keratinocytes.…”
mentioning
confidence: 99%
“…Sabe-se que as células epidermais do tecido laminar são extremamente dependentes de glicose (Pass et al, 1998) e, consequentemente, poderiam ser afetadas pela resistência insulínica característica da obesidade. Contudo, foi relatado que a captação de glicose nas lâminas do casco não parece ser dependente de insulina (Asplin et al, 2007;Walsh et al, 2009).…”
Section: Discussionunclassified